The Implementation of Visual Grammar in Slovene Classes to Mother Tongue Speakers - Starc, Sonja (Revija za elementarno izobraževanje, 2023)
The discussion focuses on the implementation of visual grammar in the study program for primary school teachers in the course Slovene language 1 - basics of text. It points out the theoretical premises of the Systemic Functional and Visual Grammar as the basis for discussing the multimodal texts, and along with a case study (34 student exam solutions) and findings from practice, presents the more challenging areas of student acquisition of theory and metalanguage. It justifies the need and shows the possibility of teaching multimodal textual analysis in school education.
Keywords: multimodal text, Slovene, Systemic Functional, Visual Grammar, meaning-making, metalanguage